The Effect of Reciprocal Teaching Technique and Metacognitive Strategy on Improving Students' Reading Comprehension - Ismayani, Andin; Christine, Linda (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
ABSTRACT The goal of this study was to determine how Reciprocal Teaching Technique and Metacognitive Strategy affected students in the tenth grade at SMK Lab Business School in Tangerang. With the help of quasi-experimental research and qualitative data, this study was quantitative. Students in the tenth grade make up the research's total population, which is 276. The writer recruited 112 students for three classes—two experimental and one control—using purposive selection to choose the sample. The control class was taught using Conventional Instruction, as opposed to the experimental class which was taught using Reciprocal Teaching Technique and Metacognitive Strategy. The author utilized a written test to determine whether the data were normal and used the chi square formula and the fisher formula to determine whether the data were homogeneous. The findings of this study revealed that students' reading comprehension scores weren't very good after being taught the technique, as evidenced by the post-test mean values for students who were taught using the reciprocal method being lower than those who were taught using the metacognitive strategy.